Employment opportunities in the weaving industry in Ilocos Norte for the EMR - Pobre, Eleanora Andres 1950- (College of Education, University of the Philippines Diliman, 1977)
This study aimed to explore employment prospects for the educable mentally retarded in the loom weaving industry in Ilocos Norte. Twenty-six employers representing different small-scale industries engaged in loom weaving in Ilocos Norte were surveyed for their opinions regarding jobs in this industry that they consider appropriate for educable mentally retarded youngsters after they graduate from school. Information yielded by the questionnaire was supplemented by interviews with workers and by an observation of the actual work situation. Twelve jobs in the weaving industry were selected as appropriate for the retardate. The findings suggest a congruence between the requirements and components of work in the weaving industry and the characteristic abilities of the educable mentally retarded.